Geographic Information System Clinic of Health Services In Samarinda City Web-Based - Erna Mulyati; Suci Ramadhani; Syafei Karim (TEPIAN, 2020)
Difficulties in finding clinics within a certain area often occur everywhere, so a number of clinics cannot meet the needs of the surrounding community. A health service clinic is a place of practice that is more than one general practitioner or specialist who works in health services. The purpose of this study is to create a web-based Geographic Information System (WebGis) regarding the distribution of clinics, especially in Samarinda City. The benefits of WebGis can present the location and information about the clinic. The search field can also search for information based on the expertise of doctors, in the form of general practitioners or specialists.